Identification of Serum Exosomal hsa-circ-0004771 as a Novel Diagnostic Biomarker of Colorectal Cancer - Pan, Bei; Qin, Jian; Liu, Xiangxiang; He, Bangshun; Wang, Xuhong; Pan, Yuqin; Sun, Huiling; Xu, Tao; Xu, Mu; Chen, Xiaoxiang; Xu, Xueni; Zeng, Kaixuan; et al. (Frontiers in Genetics, 2019)
Background: Exosomal circular RNAs (circRNAs) in peripheral blood have been considered as promising diagnostic biomarkers of cancers. Due to the lack of sensitive and specific biomarkers, a large number of colorectal cancer (CRC) patients were diagnosed in the advanced stages leading to high mortality. This study aimed to identify circulating exosomal circRNAs as novel diagnostic biomarkers of CRC. Materials and methods: Candidate circRNA was selected by integrated analysis of Gene Expression Omnibus (GEO) database using online program GEO2R. Exosomes isolated from serums of participants and cell cultured media were confirmed by transmission electron microscope (TEM), nanosight particle tracking analysis and western blot. A total of 170 patients and 45 health controls were enrolled to assess the diagnostic value of circRNAs for CRC, and the expression and diagnostic utility of candidate were tested by qRT-PCR and receiver operating characteristic (ROC) analysis, respectively. Results: The circulating exosomal hsa-circ-0004771 with large differential fold change (≥1.5) as well as highest expression abundance was selected to further explore based on the results of GEO datasets analysis. The up-regulated exosomal hsa-circ-0004771 was further verified in serums of CRC patients compared to healthy controls (HCs) and patients with benign intestinal diseases (BIDs) by qRT-PCR. The area under the ROC curves (AUCs) of circulating exosomal hsa-circ-0004771 were 0.878 (95%CI, 0.815-0.940) and 0.859 (95%CI, 0.785-0.933) to differentiate CRC patients from HCs and CRC patients with early stage, and was 0.816 (95%CI, 0.73-0.90) to differentiate CRC patients with early stage from patients with BIDs. In addition, the elevated expression of exosomal hsa-circ-0004771 in serum of CRC patients was tumor-derived by the fact that the down-regulated expression of exosomal hsa-circ-0004771 was discovered in serum of postoperative CRC patients and cultured media of CRC cells treated with GW4869. Conclusions: Circulating exosomal hsa-circ-0004771 was significantly up-regulated in CRC patients and served as a novel potential early diagnostic biomarker of CRC.